THE INFLUENCE OF MARKETING STRATEGY RELATIONSHIP AND SERVICE QUALITY TO CUSTOMER SATISFACTION IN TOYOTA AUTO SERVICE STATION - Marietje Carolien Nanulaitta (Business and Entrepreneurial Review, 2010)
The background of this research was Customer Relationship marketing and service quality of Firms have accepted that customer retention is even more profitable than customer attraction and we can observe the interest of firms in adopting relationship marketing principles and designing strategies to develop close and long-lasting relationships with the most profitable customers. The objective of The analysis of marketing activities and programs implemented in order to establish, develop, and maintain relationships with customers and the impact these activities have on the firm performance. The design of this research applies to Toyota Car Repair and the questionnaires were spreaded away to 110 respondents. Data analysis used in this research was Multiple Regression with SPSS program. The result of this research conclude that Relationship Marketing Strategy and Service Quality in Car Repair significantly affect to Customer Satisfaction